Gray System Prediction in the Alpine–Himalayan Earthquake Zone. Issue 1 (May 2021) - Chen, Jiemin; Yan, Zelin; Xu, Linfeng; Liu, Zhixin; Liu, Yan; Tian, Jiawei
Abstract: Increasingly frequent earthquakes pose a serious threat to human lives and properties. However, the prediction of seismic activity is a major problem in seismic research. In this paper, we use the gray model to study seismic activity patterns. The Alpine–Himalayan seismic zone is selected as a study area for this work. Using seismic activity in the region, we analyze characteristics of time series related to seismic activity. Results show that the gray model for predicting seismic activity is available. The timing of the seismic activity of the Alpine–Himalayan seismic zone displays certain regularity. On the basis of computational analysis on July 20, 2015, a strong earthquake will occur in 26 years. In this paper, we use the application of a gray system that provides a new modeling approach in the field of disaster prevention to predict seismic activity, which is important in disaster prevention, disaster management, and rescue.